Children’s Adaption to Input Change Using an Abstract Syntactic Representation: Evidence From Structural Priming in Mandarin-Speaking Preschoolers - Hsu, Dong-Bo (Frontiers in Psychology, 2019)
Abstract Two studies were undertaken to investigate structural priming in Mandarin-speaking three-, four- and six-year-old children using a Mandarin-specific alternation between an SVO construction and a ba-construction (SbaOV). Structural priming occurred either as a single prime or cumulatively when a block of multiple primes with the same structure is administered. The results of Study 1 find that these preschoolers exhibited structural priming effects of similar magnitudes with the SVO-ba alternation across three age groups. The results of Study 2 show that they exhibited cumulative structural priming effects of similar magnitudes when there is no delay vs. a one-day delay between their comprehension of primes and their target descriptions. The results also indicate that the participants exhibited stronger cumulative structural priming than regular structural priming. Together, these results suggest that at the age of three, children can employ an abstract syntactic representation to adapt to input changes and this adaptation operates on an implicit learning mechanism.